The ILO's maritime labour convention - Lim, Brian Jia Qing. (2011)
Over the past 80 years, there have been over 65 international labor standards relating to seafarers. The ILO Maritime Labor Convention, 2006, consolidates and updates these standards. This unified standard will provide a wide coverage in setting out seafarer’s rights to decent working conditions across a range of subjects. More importantly, this convention aims to be globally applicable and uniformly enforced. The MLC 2006 has been designed to become a global instrument of the international regulatory regime for quality shipping and will complement the other key conventions of the International Maritime Organization (IMO). The Maritime Labor Convention 2006 (MLC 2006) will come into force 12 months upon meeting the minimum requirement of 30 member states and 33 percent of the world’s tonnage ratifying it. The reach of the MLC 2006 will spread and be enforceable even on ships of non-ratifying countries as there is a “no more favorable treatment clause” in the convention.